GENE–LIFESTYLE INTERACTION IN TYPE 2 DIABETES MELLITUS: THE ROLE OF KCNJ11 VARIANTS AND PHYSICAL INACTIVITY IN URBAN PAKISTANI ADULTS (Journal of Medical & Health Sciences Review, 2025)
Background:Type 2 Diabetes Mellitus (T2DM) is a growing public health concern in Pakistan, influenced by both genetic and lifestyle factors.Objective:To evaluate the association of KCNJ11 E23K gene variants and physical inactivity with the risk of developing T2DM among urban Pakistani adults.Methodology:This descriptive cross-sectional research was conducted at Kohat University of Science and Technology (KUST) between January 2023 and December 2024. A total of 320 individuals were recruited from community screening camps and urban healthcare institutions, 160 of whom were T2DM cases and 160 of whom were non-diabetic controls. The International Physical Activity Questionnaire (IPAQ) was used to measure physical activity. PCR-RFLP was used for the KCNJ11 E23K polymorphism genotyping. One-way ANOVA was used for genotype-based comparisons, independent t-tests were used for continuous variables, and chi-square tests were used for categorical variables. To identify independent predictors of type 2 diabetes, multivariate logistic regression was used; a p-value of less than 0.05 was deemed statistically significant.Results:The KK genotype was more frequent in cases (31.25%) than controls (18.75%) (p = 0.007), with an adjusted odds ratio (OR) of 2.31 (95% CI: 1.32–4.06; p = 0.003). Low physical activity was observed in 57.5% of cases versus 31.88% of controls (p < 0.001), yielding an OR of 3.56 (1.97–6.43). Combined KK genotype and low activity was present in 22.5% of cases compared to 7.5% of controls (p < 0.001). BMI ≥ 25 kg/m² (66.25% vs. 51.25%; OR = 1.89; p = 0.007) and family history of T2DM (58.13% vs. 29.38%; OR = 3.12; p < 0.001) were also significant predictors.Conclusion:The KCNJ11 KK genotype and physical inactivity significantly increase T2DM risk, with the greatest effect observed when both factors co-exist.